High-rate hard carbon material, preparation method thereof and sodium ion battery
By building a suitable closed-cell structure in hard carbon materials, the problems of poor rate performance and poor cycle stability of hard carbon materials under high-speed conditions are solved, and the improvement of high reversible capacity and high-speed performance is achieved.
Patent Information
- Application Number
- CN202411552745.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing hard carbon materials have poor rate performance and poor cycle stability under high-rate charging and discharge conditions, resulting in poor battery reversible capacity loss and cycle performance.
By mixing the pre-carbonized hard carbon precursor with alkali, porous carbon material is generated, and a suitable closed-cell structure is constructed through acid solution pickling treatment and liquid phase impregnation and filling treatment, a high reversible capacity and high rate performance are achieved through acid solution pickling treatment and liquid phase impregnation and filling treatment. .
It achieves high reversible capacity, high first-time Coulomb efficiency and high rate performance, and improves the cycle stability and economicality of hard carbon materials.
Smart Images

Figure BDA0005115506640000151 
Figure BDA0005115506640000161
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and in particular relates to a high-rate hard carbon material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Secondary batteries play an increasingly important role in the field of new energy applications. Sodium-ion batteries and lithium-ion batteries have the same working principle and similar manufacturing process. In addition, sodium source reserves are sufficient and the cost is low. Therefore, in recent years, sodium-ion batteries are considered to be the best supplement to lithium-ion batteries in the field of large-scale energy storage. Hard carbon has become the mainstream negative electrode material for sodium-ion batteries due to its excellent comprehensive performance.
[0003] At present, the reversible capacity of hard carbon materials is generally higher than 300mAh / g, and the first coulombic efficiency is higher than 88%, which meets the basic requirements for practical applications. However, with the continuous expansion of usage scenarios, hard carbon materials have exposed problems such as poor rate performance and poor cycle stability. The reversible capacity of hard carbon mainly comes from the Na + The deposition of semi-metallic sodium in the interlayer insertion and closed-pore structure, under high-rate charge and discharge conditions, is slow due to the interlayer migration rate of Na + There will be surface enrichment and excessive metallization of sodium deposition in closed pores, and serious sodium precipitation will occur on the surface of the negative electrode material, resulting in reversible capacity loss of the battery and poor cycle performance.
[0004] Chen et al. studied a hard carbon prepared by filling activated carbon with vapor deposition, and studied the effect of deposition time on the pore size and porosity of hard carbon materials. The hard carbon has a high reversible capacity. However, the effect of pore size and porosity on the rate performance of the material was not studied, and the cost of the vapor deposition process was high. Zheng et al. studied a high-capacity hard carbon material, which introduced a rich pore structure in the pre-carbonization stage by CO2 etching, and then closed the pores by high-temperature sintering. The hard carbon with a rich closed-pore structure provided a high reversible capacity. However, the rate performance of the hard carbon material was poor. Zhao et al. studied a hard carbon material coated with asphalt liquid phase, which showed high reversible capacity, high first coulomb efficiency and high rate performance. However, the process requires the use of precious metal Ni as a catalyst during coating, which is costly, and the finished product needs to be removed for a second time, and the process is relatively complicated. Tian et al. prepared a hard carbon by impregnating activated carbon with an asphalt solution, which has a high reversible capacity and cycle stability. However, the process requires multiple impregnations and centrifugal separations, and the process flow is complicated. Other prior art discloses a hard carbon material with high reversible capacity and high first coulombic efficiency, which improves capacity by removing impurities and creating pores through acid-base treatment, and improves first coulombic efficiency by coating. However, the process does not study the effect of acid-base treatment on pore size, nor does it mention the effect of the process on improving rate performance.
[0005] In view of the current status of existing technologies, further research is still needed on how to accurately construct a closed-pore structure with appropriate pore size in hard carbon to achieve higher rate performance and better meet market demand. Summary of the invention
[0006] The purpose of the embodiments of the present application is to provide a method for preparing a high-rate hard carbon material, aiming to accurately construct a closed-pore structure with suitable pore size in hard carbon to achieve high reversible capacity, high first coulombic efficiency and high rate capability.
[0007] The embodiment of the present application is implemented as follows: a method for preparing a high-rate hard carbon material comprises:
[0008] The hard carbon precursor after pre-carbonization treatment is mixed with a base to react to obtain a porous carbon material; the base is KOH or K2CO3; the mass ratio of the hard carbon precursor to the base is 1:(0.05-0.2);
[0009] Performing an acid wash treatment on the porous carbon material with an acid solution to obtain a low-ash carbon material;
[0010] The low-ash carbon material is filled with a carbon filler by liquid phase impregnation to obtain a filled carbon material, which is then subjected to high-temperature carbonization to obtain a high-rate hard carbon material.
[0011] Preferably, in the step of mixing the pre-carbonized hard carbon precursor with a base to obtain a porous carbon material, the reaction temperature is 800-900° C. and the reaction time is 1-2 h.
[0012] Preferably, the added amount of the carbon filler is 5-10 wt % of the mass of the low ash carbon material.
[0013] Preferably, the high temperature carbonization treatment is carried out at a temperature of 1100-1300°C.
[0014] Another object of an embodiment of the present application is to provide a high-rate hard carbon material, wherein the high-rate hard carbon material is prepared by the above-mentioned method for preparing the high-rate hard carbon material.
[0015] Another object of an embodiment of the present application is a sodium ion battery, which includes the above-mentioned high-rate hard carbon material.
[0016] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:
[0017] (1) High reversible capacity: Alkali etching constructs a rich microporous structure inside the carbon material, and carbon filling transforms the open pores into a closed pore structure, thereby increasing the sodium storage active sites inside the hard carbon material and achieving an increase in capacity.
[0018] (2) Effectively improve rate performance: Through the optimization of etchants, etching conditions and carbon filling ratio, the internal porosity and closed pore diameter of hard carbon materials can be adjusted. The most likely distribution of the pore size of the best hard carbon material is 1-2nm, which provides high capacity while ensuring excellent rate performance.
[0019] (3) High first coulombic efficiency: Carbon filling and carbon coating are achieved on the surface of the material at the same time. The highly ordered coating layer can induce the formation of a thin and stable electrode electrolyte interface film (SEI), reducing the active Na + Loss, achieving high first coulombic efficiency and stable cycle performance. At the same time, the thin and stable SEI can promote the rapid desolvation process of the electrolyte, achieving the effect of improving the rate performance.
[0020] (4) Good economy: The preparation process of the present application is simple, and commonly used and inexpensive chemical reagents are used. The solvent used in the carbon filling process can be recycled, and no special equipment is required. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0022] The present application provides a method for preparing a high-rate hard carbon material, comprising:
[0023] The hard carbon precursor after pre-carbonization treatment is reacted with a base at a temperature of 800-900° C. for 1-2 hours to obtain a porous carbon material; the base is KOH or K2CO3; the mass ratio of the hard carbon precursor to the base is 1:(0.05-0.2);
[0024] Performing an acid wash treatment on the porous carbon material with an acid solution to obtain a low-ash carbon material;
[0025] The low ash carbon material is filled with a carbon filler by liquid phase impregnation to obtain a filled carbon material, which is then subjected to high temperature carbonization to obtain a high-rate hard carbon material; the amount of the carbon filler added is 5-10wt% of the mass of the low ash carbon material.
[0026] Optionally, the hard carbon raw material includes one or more of fossil raw materials and biomass raw materials. The pre-carbonization treatment conditions are: heating rate of 2-10°C / min, pre-treatment temperature of 300-800°C, pre-treatment time of 1-24h, and protective gas of nitrogen and / or argon.
[0027] Among them, in the step of reacting the pre-carbonized hard carbon precursor with alkali at a temperature of 800-900°C for 1-2h to obtain a porous carbon material, the protective gas is one or more of nitrogen, argon, and CO2, preferably a mixture of 40% CO2 and nitrogen or argon.
[0028] Optionally, the acid solution is one or more of HCl, HNO3, H2SO4, formic acid, acetic acid, and citric acid. In the step of pickling the porous carbon material with the acid solution to obtain the low-ash carbon material, the mass ratio of the porous carbon material to the acid solution is 1:5; the reaction temperature is 80°C, and the reaction time is 12h.
[0029] Optionally, the carbon filler includes one or more of asphalt, phenolic resin, epoxy resin, starch, lignin, and bamboo tar; the solvent used includes one or more of deionized water, N,N-dimethylamide, N-methylpyrrolidone, benzene, toluene, and ethanol; the mass ratio of low-ash carbon material to solvent is 1:2; and the immersion time is 12 hours. The solvent is evaporated by one or more methods of flash drying, spray drying, and rotary evaporation, and the solvent is recovered by a matching condensation reflux device.
[0030] The conditions for high-temperature carbonization treatment are as follows: a heating rate of 2°C / min; a carbonization temperature of 1000-1400°C, preferably 1100-1300°C; and a carbonization time of 3h.
[0031] Examples of certain embodiments of the present application are given below, which are not intended to limit the scope of the present application.
[0032] In addition, it should be noted that the numerical values given in the following examples are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value.
[0033] Example 1
[0034] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0035] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.1, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 1 hour; the protective gas is a mixture of 40% CO2 and 60% N2.
[0036] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0037] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0038] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1200°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0039] Example 2
[0040] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0041] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.05, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 1h; the protective gas is a mixture of 40% CO2 and 60% N2.
[0042] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0043] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0044] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1200°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0045] Example 3
[0046] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0047] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.2, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 1 hour; the protective gas is a mixture of 40% CO2 and 60% N2.
[0048] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0049] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0050] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1200°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0051] Example 4
[0052] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0053] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.1, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 900℃, and the heat treatment is 1h; the protective gas is a mixture of 40% CO2 and 60% N2.
[0054] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0055] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0056] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1200°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0057] Example 5
[0058] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0059] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.1, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 2h; the protective gas is a mixture of 40% CO2 and 60% N2.
[0060] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0061] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0062] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1200°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0063] Example 6
[0064] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0065] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.1, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 1 hour; the protective gas is a mixture of 40% CO2 and 60% N2.
[0066] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0067] S4, carbon filling: The low-ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low-ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 10wt% of the mass of the low-ash carbon material, the mass ratio of the low-ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0068] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1200°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0069] Example 7
[0070] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0071] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.1, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 1 hour; the protective gas is a mixture of 40% CO2 and 60% N2.
[0072] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0073] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0074] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1300°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0075] Example 8
[0076] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0077] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and K2CO3 into a ball mill at a mass ratio of 1:0.1, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 1 hour; the protective gas is a mixture of 40% CO2 and 60% N2.
[0078] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0079] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0080] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1100°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0081] Example 9
[0082] S1. Pre-carbonization: crush the bamboo raw material, pass it through a 50-mesh sieve, and pre-burn it in a box furnace to obtain a hard carbon precursor material. The pre-burning heating rate is 10°C / min, the temperature is 400°C, the pre-burning time is 3h, and the protective gas is nitrogen.
[0083] S2, alkali etching pore formation: add the hard carbon precursor material obtained in step S1 and KOH in a mass ratio of 1:0.1 into a ball mill, with a ball-to-material ratio of 1:5, and use a planetary ball mill to mill for 1 hour at a speed of 500r / min to obtain a mixed material. Put the mixed material into a box furnace for heat treatment to obtain a porous carbon material. The heating rate is 10℃ / min, the temperature is 800℃, and the heat treatment is 1 hour; the protective gas is a mixture of 40% CO2 and 60% N2.
[0084] S3, pickling and impurity removal: the porous carbon material obtained in step S2 is pickled, filtered, washed with water until neutral, and dried to obtain a low-ash carbon material. The acid used is concentrated hydrochloric acid, the mass ratio of the porous carbon material to the concentrated hydrochloric acid is 1:5, the reaction temperature is 80°C, and the reaction time is 12h.
[0085] S4, carbon filling: the low ash carbon material obtained in step S3 is subjected to liquid phase impregnation filling, and the mixed slurry of the low ash carbon material and the impregnation liquid is flash dried to obtain the filled carbon material. The impregnation liquid is an N,N-dimethylformamide solution of asphalt, the asphalt addition amount is 5wt% of the mass of the low ash carbon material, the mass ratio of the low ash carbon material to the N,N-dimethylformamide solvent is 1:2, and the impregnation is 12h. The flash drying temperature is 180°C, and the solvent is recovered by a condensation device.
[0086] S5, high temperature carbonization: placing the filled carbon material obtained in step S4 in a high temperature carbonization furnace, in a nitrogen atmosphere, at 1200°C for 3 hours to obtain a high rate performance hard carbon negative electrode material, wherein the heating rate is 2°C / min.
[0087] Comparative Example 1
[0088] The K2CO3 in step S2 is replaced by Na2CO3, and the rest is the same as in Example 1.
[0089] Comparative Example 2
[0090] The K2CO3 in step S2 is replaced by NaOH, and the rest is the same as in Example 1.
[0091] Comparative Example 3
[0092] The K2CO3 in step S2 is replaced by CaCO3, and the rest is the same as in Example 1.
[0093] Comparative Example 4
[0094] The mass ratio of the hard carbon precursor material and K2CO3 in step S2 is adjusted to 1:0, and the rest is the same as in Example 1.
[0095] Comparative Example 5
[0096] The mass ratio of the hard carbon precursor material and K2CO3 in step S2 is adjusted to 1:0.3, and the rest is the same as in Example 1.
[0097] Comparative Example 6
[0098] The alkali etching temperature in step S2 is adjusted to 600° C., and the rest is the same as in Example 1.
[0099] Comparative Example 7
[0100] The alkali etching temperature in step S2 is adjusted to 1000° C., and the rest is the same as in Example 1.
[0101] Comparative Example 8
[0102] The alkali etching time in step S2 is adjusted to 3 hours, and the rest is the same as in Example 1.
[0103] Comparative Example 9
[0104] The amount of asphalt added in step S4 is adjusted to 15wt% of the mass of the low ash carbon material, and the rest is the same as in Example 1.
[0105] Comparative Example 10
[0106] Step S4 is not performed, and the rest is the same as in Example 1.
[0107] Comparative Example 11
[0108] The high temperature carbonization temperature in step S5 is adjusted to 1000° C., and the rest is the same as in Example 1.
[0109] Comparative Example 12
[0110] The high temperature carbonization temperature in step S5 is adjusted to 1400° C., and the rest is the same as in Example 1.
[0111] Comparative Example 13
[0112] JH3-5 bamboo-based activated carbon from Zhejiang Jizhu Biotechnology Co., Ltd. was directly purchased as the low-ash carbon material, and steps S4 and S5 were performed under the same conditions as in Example 1.
[0113] Firstly, the pore size distribution of hard carbon was analyzed by small angle X-ray scattering (SAXS) measurement and SASFIT software, the specific surface area of hard carbon was obtained based on BET theory by N2 desorption test, and the true density of hard carbon was obtained by true density meter. The results are shown in Table 1.
[0114] Furthermore, the hard carbon materials prepared in the various embodiments and comparative examples are applied to the negative electrode of the sodium ion battery as the negative electrode active material of the sodium ion secondary battery. According to the mass ratio of 92%:3%:1.5%:3.5%, 184 mg of the above hard carbon powder, 6 mg of conductive carbon black, 6 mg of 2% (w / w) carboxymethyl cellulose solution, and 17.5 mg of 40% (w / w) styrene-butadiene rubber are weighed, and an appropriate amount of deionized water is added dropwise, and stirred for 20 minutes until it becomes a uniform slurry. A 100 μm scraper is used to evenly coat it on the surface of the copper (Cu) foil, and it is dried in a blast drying oven at 105°C for 2 hours. The Cu foil with the active material is cut into a disc-shaped negative electrode sheet, and then transferred to a glove box for standby use.
[0115] The assembly of the simulated battery was carried out in a MIKROUNA glove box filled with Ar atmosphere, using the prepared carbon material pole piece as the negative electrode, the commercial electrolyte 1.0mol / L NaPF6 in DME as the electrolyte, and the Na metal sheet as the counter electrode to assemble the 2016 button cell. After the above battery was left for 12 hours, the first charge and discharge test was carried out at a rate of 0.1C, with a voltage range of 0 to 2V. The rate charge and discharge test was carried out at a rate of 0.1-5C. The test results are shown in Table 1.
[0116] Table 1
[0117]
[0118]
[0119] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
[0120] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a high-rate hard carbon material, characterized in that: include: The hard carbon precursor after pre-carbonization treatment is reacted with a base at a temperature of 800-900° C. for 1-2 hours to obtain a porous carbon material; the base is KOH or K2CO3; the mass ratio of the hard carbon precursor to the base is 1:(0.05-0.2); Performing an acid wash treatment on the porous carbon material with an acid solution to obtain a low-ash carbon material; The low ash carbon material is filled with a carbon filler by liquid phase impregnation to obtain a filled carbon material, which is then subjected to high temperature carbonization to obtain a high-rate hard carbon material; the amount of the carbon filler added is 5-10wt% of the mass of the low ash carbon material.
2. The method for preparing a high-rate hard carbon material according to claim 1, characterized in that: In the step of reacting the pre-carbonized hard carbon precursor with a base at a temperature of 800-900° C. for 1-2 hours to obtain a porous carbon material, the protective gas is one or more of nitrogen, argon, and CO2.
3. The method for preparing a high-rate hard carbon material according to claim 1, characterized in that: The conditions of the high temperature carbonization treatment are: temperature of 1100-1300° C.; heating rate of 2° C. / min; and carbonization time of 3 h.
4. The method for preparing a high-rate hard carbon material according to claim 1, characterized in that: The carbon filler is one or more of asphalt, phenolic resin, epoxy resin, starch, lignin and bamboo tar.
5. The method for preparing a high-rate hard carbon material according to claim 1, characterized in that: In the step of acid-washing the porous carbon material with an acid solution to obtain a low-ash carbon material, the mass ratio of the porous carbon material to the acid solution is 1:5; the reaction temperature is 80° C., and the reaction time is 12 hours.
6. The method for preparing a high-rate hard carbon material according to claim 1, characterized in that: The acid solution is one or more of HCl, HNO3, H2SO4, formic acid, acetic acid, and citric acid.
7. The method for preparing a high-rate hard carbon material according to claim 1, characterized in that: The pre-carbonization treatment conditions are: a heating rate of 2-10°C / min, a pre-treatment temperature of 300-800°C, a pre-treatment time of 1-24h, and a protective gas of nitrogen and / or argon.
8. The method for preparing a high-rate hard carbon material according to claim 1, characterized in that: The low-ash carbon material is filled with a carbon filler by liquid phase impregnation to obtain a filled carbon material, wherein the solvent used is one or more of deionized water, N,N-dimethylformamide, N-methylpyrrolidone, benzene, toluene, and ethanol; the mass ratio of the low-ash carbon material to the solvent is 1:2; and the impregnation time is 12 hours.
9. A high-rate hard carbon material, characterized in that: The high-rate hard carbon material is prepared by the method for preparing a high-rate hard carbon material according to any one of claims 1-8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the high-rate hard carbon material according to claim 9.
Citation Information
Patent Citations
Hard carbon negative electrode composite material and preparation method and application thereof
CN113184828A
Sodium-ion battery negative electrode biomass hard carbon material, preparation method and sodium-ion battery
CN118529711A
Preparation method of sodium ion battery negative electrode porous hard carbon
CN118529716A
Preparation method of balsa wood biomass lithium battery carbon electrode material
CN118579778A
Hard carbon negative electrode material derived from cyclobalanopsis glauca and preparation method thereof
CN118637600A
Cited By
Controllable construction method for carbon layer structure on hard carbon surface and application of controllable construction method
CN120463182A